Food insufficiency and its relation to academic performance in rural Food insufficiency and its relation to academic performance in rural Kemaman - Jaafar, Nurul Hazirah; Afandi, Aflah (2011)
Food insufficiency has been addressed as one of the potential factors that can lead to divest developmental consequences such as low academic performance and decline in nutritional status among school-age children. In this cross-sectional study design, student’s academic performance in mathematics and science subjects was recorded. This data was then further analyzed to investigate how does it affected when these children experience different level of food insecurity as reported by their mothers. Thirty students of standard five from selected school in rural Kemaman were recruited in this study. Food insecurity was measured by mothers’ interview using validated malay translation Radimer/Cornell hunger and food insecurity instrument. It was reported that 67% (n=20)of the respondents experiencing some kind of food insecurity. Overall performance of these students in mathematics and science subject are relatively poor, whereby they only achieved a median of 33.1(±30.8) and 38.0(±43.2) marks for both subjects respectively. However, their low achievement in academic has not significantly different between food secure and insecure household. Nevertheless, underweight indicator is potentially affecting their academic performance. Students who failed mathematics was significantly had lower weight-for-age (-1.50 SD ±2.30) compared to the other group (-0.22 SD ±1.45) at p<0.01. Spearman test shows that there is a positive correlation between underweight status and mathematics marks (p<0.05) but not in the science subject. Despite of 40% (n=12) of the children were underweight, the data gives some indication that their family food situation did not influence children’s performance in both subjects. This result may suggest that some protective factors such as monetary assistance and food subsidies provided by the government and private sector play a significant role to help vulnerable family for their survival. Persistence and earnest efforts from many authorities are recommended to improve not only the health and nutrition of these school children but also the overall well-being in order for them to serve as productive nation.